Copeptin combined with either non-high sensitivity or high sensitivity cardiac troponin for instant rule-out of suspected non-ST segment elevation myocardial infarction - Giannitsis, Evangelos; Slagman, Anna; Hamm, Christian W.; Gehrig, Stefan; Vollert, Joern O.; Huber, Kurt (Biomarkers, 2020)
Whether Copeptin combined with high sensitivity troponin below the respective decision cut-offs improves rule-out of NSTEMI and may predict all-cause death at 30-day is under debate. Data on 10,329 patients from 5 trials were pooled to evaluate the diagnostic and prognostic performance of an initial Copeptin below decision cut-off in combination with a (hs)-cTn below the uppler limit of normal (ULN) compared to a) the initial (hs)-cTn alone in the standard serial sampling strategy based on the 99th percentile and b) a single marker strategy (SMS) based on hs-cTn < limit of detection. Endpoints were sensitivities and negative predictive values (NPV) for rule-out of NSTEMI, 30-day all-cause mortality and rates of eligibility for DMS or SMS. NPV for NSTEMI was higher for DMS than for the initial cTn, regardless assay sensitivity. The highest NPVs were observed with DMS vs. hs-cTn (99.4% [95% CI: 99.0%-99.6%] vs. 98.8% [98.4%-99.1%],) , and improved performance was consistent across all important subgroups including presentation <3 h, again irrespective of assay sensitivity. The point estimate of all NPVs for all-cause death exceeded 99.75%. In the label populations, DMS versus SMS demonstrated comparably high NPVs for rule-out of NSTEMI (99.4% [99.0%-99.6%] vs. 99.9% [99.2%-100.0%]), very low mortality after rule-out (0.1% [0.0%-0.4% vs. 0.0% [0.0%-1.2%]), but eligibility for rule-out was 2.4-fold higher (61.4% [59.9%-62.9%] vs. 25.3% [23.7%-26.9%]) with DMS than SMS. Findings from a large pooled cohort corroborate the safety of the dual marker strategy for instant rule-out of NSTEMI, extending evidence to hs-cTn. Copeptin below cut-off in combination with hs-cTn below ULN may be used in more than 2.4-times more patients presenting with suspected ACS than a single marker strategy based on very low hs-cTn, without the need to exclude very early presenters or other important subgroups.
Gesehen am 09.08.2024